2020
DOI: 10.30598/ajibt.v9i2.1159
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Nitrogen pada Pupuk Cair dan Musim Terhadap Kandungan Bahan Aktif Epigalokatekin Galat (EGCG) Pucuk Teh (Camellia sinensis L.)

Abstract: Epigalokatekin Galat (EGCG) adalah senyawa bioaktif turunan katekin pucuk teh yang memiliki sifat antioksidan sangat tinggi. EGCG banyak digunakan sebagai bahan baku terapi penyembuhan berbagai penyakit degenerative.  Kandungan EGCG pada pucuk teh sangat ditentukan oleh faktor iklim dan manajemen teknik budidaya terutama pasokan hara nitrogen sebagai elemen kunci pada tahap awal biosintesis prekusor katekin. Penelitian ini bertujuan untuk menentukan pengaruh penambahan tingkat N pada pupuk cair terhadap kandun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
0
0
1
Order By: Relevance
“…The results of the Correlation Test found that the content of Polyphenols, Catechins (EGCG), Flavonoids, and Caffein is influenced by soil nutrients pH, C org, N, P2O5 available, P2O5, K2O,CaO,Ca,and Mg. The results of this study are in line with (Hukom, 2020) research that the application of liquid fertilizer without the addition of N in the dry season affects the increase in the active ingredient content of EGCG tea shoots to the highest to reach 12.53%. The EGCG content of rainy season tea shoots is always lower than the dry season, because of high rainfall with long time intervals, resulting in a lot of N nutrients leaching out of the plant root area resulting in N stress which affects the decrease in chlorophyll biosynthesis.…”
Section: The Effect Of Soil Nutrient Content On Tea Leaf Qualitysupporting
confidence: 89%
“…The results of the Correlation Test found that the content of Polyphenols, Catechins (EGCG), Flavonoids, and Caffein is influenced by soil nutrients pH, C org, N, P2O5 available, P2O5, K2O,CaO,Ca,and Mg. The results of this study are in line with (Hukom, 2020) research that the application of liquid fertilizer without the addition of N in the dry season affects the increase in the active ingredient content of EGCG tea shoots to the highest to reach 12.53%. The EGCG content of rainy season tea shoots is always lower than the dry season, because of high rainfall with long time intervals, resulting in a lot of N nutrients leaching out of the plant root area resulting in N stress which affects the decrease in chlorophyll biosynthesis.…”
Section: The Effect Of Soil Nutrient Content On Tea Leaf Qualitysupporting
confidence: 89%
“…Hal tersebut sangat penting karena berkaitan dengan kebutuhan air tanaman dan implementasi manajmen hara tanaman secara terpadu di perkebunan. Hasil Penelitian di Perkebunan Teh Tritis menunjukkan bahwa bobot segar dan bobot kering produktivitas pucuk teh tertinggi terjadi di musim hujan namun rendemen, kandungan bahan aktif Epigallocatechine gallate (EGCG) dan sifat antioksidannya di musim hujan jauh lebih rendah dari musim kemarau [6,9,10] . Hal ini disebabkan karena kondisi curah hujan yang tinggi menyebabkan pertumbuhan pucuk lebih cepat dengan kadar air jaringan yang tinggi.…”
Section: Manfaat Penentuan Awal Musim Hujan Dan Awal Musim Kemarau Lokalunclassified